Pendekatan Berdiferensiasi pada Pembelajaran IPS sebagai Bentuk Internalisasi Konsep Merdeka Belajar - Mira Nurazijah; Syaipia Lailla; Tin Rustini (Journal on Education, 2023)
Learning is an interactive process in which a person can acquire knowledge, skills, attitudes, and understanding through instructions or experiences conveyed by educators or from the learning environment itself. This involves the interaction between teachers and students, and students and their surroundings. However, in implementing this learning, it is necessary to understand that each student has different learning style characteristics. One of them is also in the implementation of learning Social Sciences (IPS). To overcome this problem regarding the delivery of these different learning styles, one can use a differentiated approach from internalizing the concept of independent learning which is able to involve students to be independent and free in using their learning styles to acquire knowledge. The method used in this research is literature review or literature review which is obtained by searching for literature sources that are relevant to the research topic. In this case it was found that differentiated learning, one of which is used in social studies learning, is able to create an atmosphere of a learning environment that can enable students to learn according to their own interests and needs. So that through this differentiated learning children can focus on their own potential and skills where the teacher can later facilitate children by fostering and guiding so that children can maximize the potential and skills that exist in them.